2022
DOI: 10.3390/medicina58050618
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation Therapy in the Treatment of Oral Mucositis—A Case Report

Abstract: In 2021, our group published a laboratory study on the impact of PBM on human gingival fibroblasts. The in vitro results confirmed the fact that the appropriately selected wavelength and properly selected parameters of the laser settings can increase cell proliferation, modulate inflammatory markers, and decrease the susceptibility of human gingival fibroblasts to apoptosis. Therefore, this case report was aimed at the clinical evaluation of the proposed settings and treatment regimen in a very difficult situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The treatment with a 635 nm laser diode was advised. The treatment provided total remission of mucositis on the 21st day of treatment, in which the lesion was healed, obtaining pink mucosa pain relief (Jabłoński et al, 2022). This is observed in the studies by Melo, M. C. F. (2020) andEl Mobadder, M. et al (2018), in which all these effects were evaluated.…”
Section: Mucositismentioning
confidence: 70%
See 2 more Smart Citations
“…The treatment with a 635 nm laser diode was advised. The treatment provided total remission of mucositis on the 21st day of treatment, in which the lesion was healed, obtaining pink mucosa pain relief (Jabłoński et al, 2022). This is observed in the studies by Melo, M. C. F. (2020) andEl Mobadder, M. et al (2018), in which all these effects were evaluated.…”
Section: Mucositismentioning
confidence: 70%
“…It is suggested that the analgesic effects of PBM are achieved with wavelengths of 630-650 nm and 780-900 nm, the inflammatory effect is at the same wavelengths and the healing effect between 780-805 nm (Hamblin, Agrawal, & De Sousa, 2016, Jabłoński et al, 2022.…”
Section: Mucositismentioning
confidence: 99%
See 1 more Smart Citation
“…Although the costs of the preventive protocol exceed the costs of OM treatment, other expenditures are associated with the occurrence of OM. The dissemination of PBM for the prevention and treatment of cancerrelated comorbidities can improve the patient's quality of life [31], reduce the need for nasogastric or parenteral nutrition [32], maintain the patient's body weight [33], shorter hospital stays [7,34] and, consequently, reduce hospital-related costs [18]. Further statistical models should simulate the cost-opportunity relationship of the administration of PBM in patients undergoing cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Still, more often, three appointments per week or daily PBMT for the first 5 days and then every other day is recommended. 12 A review published in 2017 by Al-Maweri et al emphasized that PBMT is effective in the management of symptomatic OLP. However, another systematic review by Akram et al in 2018 that sought to assess the efficacy of PBMT in comparison to topical corticosteroids in the therapy of atrophic-erosive types of OLP concluded that it remains debatable whether PBMT is more effective than topical corticosteroids.…”
Section: Introductionmentioning
confidence: 99%